2017
DOI: 10.1063/1.4985467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial treatment in the preparation of natural indigo dye from Indigofera tinctoria

Abstract: Protection capacity of mosquito repellent ink from citronella (Cymbopogon nardus L.) and clove leaf oils (Syzygium aromaticum) againts Aedes aegypti AIP Conference Proceedings 1855, 020023 (2017) Abstract. The current tinting industries return to the use of natural dyes because of their characteristics including safe and environmentally friendly. Indonesia can widely promote the potential of natural colours due to the availability of abundant natural dye plants. One of the potential plants that generates blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
(1 reference statement)
0
13
0
2
Order By: Relevance
“…Further characterization revealed that the RhNPs were amorphous [ 29 ]. Apart from RhNPs, other metallic NPs, including zinc oxide and cobalt, have been reportedly synthesized from A. linearis and fully characterized [ 123 ], but nothing is reported regarding their biological applications.…”
Section: Biological Application Of Mnps Synthesized From Some Selected South African Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterization revealed that the RhNPs were amorphous [ 29 ]. Apart from RhNPs, other metallic NPs, including zinc oxide and cobalt, have been reportedly synthesized from A. linearis and fully characterized [ 123 ], but nothing is reported regarding their biological applications.…”
Section: Biological Application Of Mnps Synthesized From Some Selected South African Medicinal Plantsmentioning
confidence: 99%
“…FTIR analysis of the fabricated AgNPs indicated relevant absorption peaks corresponding to N-H stretching from peptide linkages and C-C stretching vibrations of aromatic amines. The fabricated AgNPs were tested on Indian and Saudi Arabian strains of Anopheles, Aedes, and Culex mosquitoes and reported to be a source of green nanoinsecticides against mosquito vectors [ 123 ]. Also, the bacteria growth inhibition effect of the biogenic A. herba-alba AgNPs was demonstrated against B. subtilis , K. pneumonia , and S. typhi .…”
Section: Biological Application Of Mnps Synthesized From Some Selected South African Medicinal Plantsmentioning
confidence: 99%
“…Bahan pewarna alami dapat diperoleh dari pengolahan bahanbahan alam di daerah sekitar pengrajin batik, tidak bergantung impor seperti bahan pewarna sintetis. Produk ramah lingkungan sesuai untuk konsumen modern yang lebih memperhatikan kelestarian lingkungan (Purnama et al, 2017), dan sesuai isu green product pasar global (Purwanto, 2018). Zat warna alam bersifat non karsinogenik sehingga nyaman dan aman jika dipakai oleh manusia, efek intensitas warna terhadap kornea mata terasa lebih menyejukkan hingga dapat menyehatkan (Siregar, 2016) (Dewi, 2014).…”
Section: Saatnya Kembali Menggunakan Zat Pewarna Alamiunclassified
“…Namun demikian, pasar pewarna alami meningkat dan memiliki hubungan linear dengan orang-orang modern yang lebih memperhatikan kelestarian lingkungan. (Purnama et al 2017) Zat pewarna alam dapat diperoleh dari binatang, mineral-mineral dan tumbuhan baik secara langsung maupun tidak langsung. Zat pewarna alam ini diproleh dengan cara ekstraksi atau perebusan secara tradisional.…”
Section: Pendahuluanunclassified